2022
DOI: 10.1007/s41686-022-00067-z
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Microlearning Intervention to Limit COVID-19 Online Misinformation

Abstract: As part of a design-based research project, we designed, developed, and evaluated a web-based microlearning intervention in the form of a comic into the problem of COVID-19 online misinformation. In this paper, we report on our formative evaluation efforts. Specifically, we assessed the degree to which the comic was effective and engaging via responses to a questionnaire (n = 295) in a posttest-only non-experimental design. The intervention focused on two learning objectives, aiming to enable users to recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Evaluation is an activity of collecting, analyzing, and presenting important data and information which is being considered for better decisions with relevant indicators such as readiness of the teachers and organizing team, and completeness of infrastructure or facilities. Evaluation of tutorial programs to assess quality assurance in the implementation of the Distance Learning Program Unit provides open opportunities for students to be involved in evaluating the tutorial process itself on a regular and continuous basis at each tutorial stage using the "Tutor Evaluation Questionnaire" instrument (Azar et al, 2021;Sahling & De Carvalho, 2021;Poole, 2020;Veletsianos et al, 2022).…”
Section: The Standardization Of Innovative Education In the Covid-19 Eramentioning
confidence: 99%
“…Evaluation is an activity of collecting, analyzing, and presenting important data and information which is being considered for better decisions with relevant indicators such as readiness of the teachers and organizing team, and completeness of infrastructure or facilities. Evaluation of tutorial programs to assess quality assurance in the implementation of the Distance Learning Program Unit provides open opportunities for students to be involved in evaluating the tutorial process itself on a regular and continuous basis at each tutorial stage using the "Tutor Evaluation Questionnaire" instrument (Azar et al, 2021;Sahling & De Carvalho, 2021;Poole, 2020;Veletsianos et al, 2022).…”
Section: The Standardization Of Innovative Education In the Covid-19 Eramentioning
confidence: 99%
“…We reiterated to participants that researchers have found that social media content spreads faster if it makes someone fearful or angry, and that online misinformation benefits from this effect. Based on previous aspects of this research (Veletsianos et al, 2022a), we recommended some simple steps to recognize content that plays on a person's emotions with the goal of helping people slow down their response to online information and thus slow the spread of misinformation. These steps include encouraging people to pause for a moment, reassess their emotional state, and then decide if it's worth responding.…”
Section: Research Questionsmentioning
confidence: 99%
“…DBR is systematic in its approach and relies on iterative analysis, design, development, implementation, and evaluation (Wang & Hannafin, 2006). This project has resulted in the development of design principles and a theoretical framework for educational interventions into health misinformation (Veletsianos et al, 2022b, Houlden et al, 2022, as well as evaluation of a previous iteration of the intervention (Veletsianos et al, 2022a), with a focus on developing both principles and interventions specific to women in online spaces as part of a larger project on health misinformation education (Houlden et al 2022). In this paper, we report on learning outcomes associated with a short multimedia interactive narrative aimed at educating users about some of the techniques used to spread misinformation, as well as towards empowering users with strategies for identifying and disrupting those techniques so that they avoid inadvertently spreading misinformation further.…”
Section: Introductionmentioning
confidence: 99%